2019
DOI: 10.1093/jnci/djz034
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Clinicopathological and Prognostic Features of Thin Nodular Primary Melanomas: An International Study from 17 Centers

Abstract: Background Nodular melanoma (NM) is more likely to be fatal compared with other melanoma subtypes, an effect attributed to its greater Breslow thickness. Methods Clinicopathological features of NM and superficial spreading melanoma (SSM) diagnosed in 17 centers in Europe (n = 15), the United States, and Australia between 2006 and 2015, were analyzed by multivariable logistic regression analysis, with emphasis on thin (T1 ≤ 1.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(48 citation statements)
references
References 39 publications
(40 reference statements)
5
39
0
Order By: Relevance
“…In contrast, atypical network, regression structures and irregular streaks were rarely found in our overall sample of NM. The latter finding is consistent with pre-existing literature 8,10,22,23 and is explained by the fact that these features correspond to histopathologic alterations at the level of the dermo-epidermal junction, which are absent or minimal in NM. 11,24,25 The multivariate analysis revealed three important predictors of NM ≤2 mm Breslow thickness as compared to non-melanomas: dotted vessels, white shiny streaks/lines and irregular blue structureless area (Fig.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast, atypical network, regression structures and irregular streaks were rarely found in our overall sample of NM. The latter finding is consistent with pre-existing literature 8,10,22,23 and is explained by the fact that these features correspond to histopathologic alterations at the level of the dermo-epidermal junction, which are absent or minimal in NM. 11,24,25 The multivariate analysis revealed three important predictors of NM ≤2 mm Breslow thickness as compared to non-melanomas: dotted vessels, white shiny streaks/lines and irregular blue structureless area (Fig.…”
Section: Discussionsupporting
confidence: 92%
“…However, in line with previous publications, we found that an important proportion of NMs (up to 30%) remain symmetric in terms of dermatoscopic colours and structures. 2,[8][9][10]21,22 Irregular brown dots/globules, irregular blue structureless area, ulceration, white shiny blotches/strands and white shiny streaks were the most frequently encountered dermatoscopic structures in the group of thin NMs (Fig. 1).…”
Section: Discussionmentioning
confidence: 99%
“…Because they are tumorigenic from close to their initiation, NMs present as rapidly growing lesions. Nodular melanomas have a worse prognosis, on the average, than other melanomas, but this difference disappears, perhaps not completely, 179 when multivariable analyses are done.…”
Section: Nodular Melanomamentioning
confidence: 99%
“…Morphological evaluation of histological regression 13,14 Histological regression: definition and phases…”
Section: Study Populationmentioning
confidence: 99%